Problem-posing as an instructional strategy to improve engagement in a flexible learning environment - Apolinario, Randy (Animo Repository, 2022)
Promoting student engagement in mathematics is crucial for academic success. This study explores the benefits of problem-posing as an instructional strategy to enhance student engagement in Mathematics, addressing the urgent need for educational reform due to low assessment results both locally and internationally. It emphasizes the importance of prioritizing student engagement in classroom research as advocated by global educational experts. Using a classroom-based descriptive-qualitative approach, this research examines the impact of problem-posing in a flexible learning environment. Seven problem-posing activities, categorized into structured and semi-structured sentences, and free structured situations, were implemented. Data collection methods included online surveys, interviews, and observations. Thematic analysis and data triangulation techniques were used to ensure credible and valid findings. The findings indicate that problem-posing as an instructional strategy significantly increased student engagement. Teaching practices shifted to a student-centered approach, fostering collaborative and critical thinking, peer teaching, self-regulation, and self-directed learning skills. Students enjoyed more autonomy in their learning regarding time, space, and pace. By actively engaging students in writing, modeling, problem-posing, discussing, and exploring Mathematics ideas, educators can effectively enhance student success. This research underscores the importance of incorporating problem-posing in a flexible learning environment, providing valuable insights for educators aiming to improve student engagement and outcomes in Mathematics education. Key Words: Problem Posing, Instructional Strategy, Engagement, Flexible Learning Environment